Biological Control of Cattle Ticks through Native Entomopathogenic Nematodes (Steinernema carpocapsae) (Global Journal of Medical Research, 2022)
Entomopathogenic nematodes have been successfully used as biological control agents for insects of economically important crops. In the present study, the bioefficacy of two different strains of entomopathogenic nematodes, Steinernema carpocapsae STSLU and S. carpocapsae STUDR against two different cattle hard ticks, Rhipicephalus microplus and Hyalomma savignyi was evaluated based on percentage mortality under laboratory conditions. The adult female of cattle ticks were inoculated with infective juveniles (IJs) of the strains S. carpocapsae at different inoculum levels. All the treatments were replicated four times at 20º C in a B.O.D. incubator. The percentage mortality of the cattle ticks was determined every 24 hours up to 120 hours from the time of inoculation.
Keywords: ticks; biological control; epns; entomopathogenic nematodes